The threshold effect of R&D investment on regional economic performance in China considering environmental regulation. Issue 7 (2nd July 2020) - Wu, Minlian; Wang, Xihui; Chen, Xiafei; Cao, Yang
ABSTRACT: Given the regionally differentiated environmental regulatory means, this paper evaluates the contribution of firms' R&D investment to economic growth with interprovincial panel data on 30 provinces in China from 2009 to 2016, which is based on the time-varying threshold model. Additionally, the coupling coordination degree model (CCDM) is used to measure the effects of technological innovation through enterprise collaboration for R&D input and investment-focused environment regulations. We then explore the inter-regional technology transfer path with different cooperation effects in areas and find: (i) The economic performance of the R&D investments of regional enterprises shows a downward trend with the strengthening of cost-focused ER while an inverted 'U'-shaped relationship that first strengthens and then weakens is presented with the strengthening of investment-focused ER. (ii) The degree of coupling calculated by CCDM is generally low, and synergies are improving from the west to the east, from a geographic perspective.